A C=O⋅⋅⋅Isothiouronium Interaction Dictates Enantiodiscrimination in Acylative Kinetic Resolutions of Tertiary Heterocyclic Alcohols. (19th February 2018) - Greenhalgh, Mark D.; Smith, Samuel M.; Walden, Daniel M.; Taylor, James E.; Brice, Zamira; Robinson, Emily R. T.; Fallan, Charlene; Cordes, David B.; Slawin, Alexandra M. Z.; Richardson, H. Camille; Grove, Markas A.; Cheong, Paul Ha‐Yeon; et al.
Abstract: A combination of experimental and computational studies have identified a C=O⋅⋅⋅isothiouronium interaction as key to efficient enantiodiscrimination in the kinetic resolution of tertiary heterocyclic alcohols bearing up to three potential recognition motifs at the stereogenic tertiary carbinol center. This discrimination was exploited in the isothiourea‐catalyzed acylative kinetic resolution of tertiary heterocyclic alcohols (38 examples, s factors up to >200). The reaction proceeds at low catalyst loadings (generally 1 mol %) with either isobutyric or acetic anhydride as the acylating agent under mild conditions.